2016
DOI: 10.1590/1518-8345.0821.2700
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection in patients submitted to heart transplantation

Abstract: Objectives: to analyze the occurrence and predisposing factors for surgical site infection in patients submitted to heart transplantation, evaluating the relationship between cases of infections and the variables related to the patient and the surgical procedure. Method: retrospective cohort study, with review of the medical records of patients older than 18 years submitted to heart transplantation. The correlation between variables was evaluated by using Fisher's exact test and Mann-Whitney-Wilcoxon test. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
2
0
1
Order By: Relevance
“…Surgical management formed the basis of the treatment of surgical site and abdominal infections. The rates of these sources, rate of mortality, and the proportion of cases managed conservatively was similar to those described previously [23,[40][41][42][43]. No differences were found comparing the mortality of patients treated with a surgical approach to those managed conservatively, although the small sample size and the subjective indication of surgery limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 83%
“…Surgical management formed the basis of the treatment of surgical site and abdominal infections. The rates of these sources, rate of mortality, and the proportion of cases managed conservatively was similar to those described previously [23,[40][41][42][43]. No differences were found comparing the mortality of patients treated with a surgical approach to those managed conservatively, although the small sample size and the subjective indication of surgery limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 83%
“…[ 30 32 ] In our study, the results showed no association between preoperative skin preparation and SSI. It is similar to the Poveda and coworkers’ [ 33 ] study showing no association between shaving and SSI. We also found that there was no significant difference in SSI rate or sign of infection between hair shaving and 2% chlorhexidine groups.…”
Section: Discussionsupporting
confidence: 91%
“…Following MHS, infection risk estimates are often biased as different reports usually consider only certain factors such as a given period of postoperative stay, type of surgery, type of infection or even certain groups of causative microorganisms. For instance, the reported incidence of surgical wound infection ranges from 2.6 to 5.5% and is higher in heart transplant recipients [ 5 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%